Comparison of Romania’s Digital Education Model with Other Eastern European Countries - Daniela Florina Stancu; Rodica Andreea Munteanu; Irina Roxana Petrescu (Lafadz Jaya Publisher, 2025)
This study presents a comparative analysis of Romania's digital education model in relation to other Eastern European countries, namely Poland, Hungary, the Czech Republic, and Russia. The research employs a descriptive qualitative approach, analyzing secondary data such as academic publications, government policies, and institutional reports. The findings reveal that while Romania has made significant strides in aligning its education system with European Union standards—through initiatives like SmartEDU and integration with the Bologna Process—its implementation remains inconsistent, especially in rural regions. Compared to Poland and the Czech Republic, which demonstrate strong infrastructure, decentralized governance, and sustained teacher training, Romania’s digital integration is hampered by bureaucratic inertia, infrastructure gaps, and a lack of equitable access. Hungary shows a more centralized governance model, while Russia presents significant regional disparities. Notably, Romania has shown promise in informal education, such as the Romanian Science Festival, helping bridge digital divides through community-led innovation. The paper concludes that for Romania to advance its digital education goals, it must prioritize teacher training, infrastructure development, and localized policy execution. This study contributes to understanding how post-communist education systems navigate digital transformation amid structural and socioeconomic constraints.